P24 Exploration of Graduate Students’ Experience in a Flipped Course Using Learning Reflections - Vollmer, Rachel L.; Drake, Teresa (Journal of nutrition education and behavior, 2019)
To evaluate graduate students’ experience in a flipped advanced metabolism course using periodic learning reflections. Although flipped learning seems to be beneficial for student learning, many studies comparing the flipped classroom to traditional lecture-based courses have focused on exam scores. This is not likely indicative of deeper level learning or how a student experiences the flipped classroom throughout the semester. Two cohorts of graduate students (n = 17) in an advanced metabolism course that utilized a flipped learning approach during the fall 2017 and 2018 semesters were recruited. Students prepared for class by watching online videos and reading a textbook. In class, students worked in teams to apply material, in which the teacher served as a guide. Each student completed eight structured learning reflections throughout the semester. After the course ended, content analysis was applied to the learning reflections at each time point by two investigators. Themes were developed for each time point. Themes from the reflections aligned with the Staged Self-Directed Learning Model. At the beginning of the semester, students were motivated to learn (stage 2), but were frustrated with the time needed for preparation. Resistance to flipped learning peaked at week four of the semester and students reverted to being teacher-centered learners (stage 1). By the end of the semester, students continued to progress to involved learners (stage 3), and eventually self-directed learners (stage 4). Even though students reported they were better self-directed learners at the end of the semester, it seems that students may have trouble with the flipped learning format during the first half of the semester. Because students reported feeling frustrated and anxious, instructors may need to adopt more scaffolding techniques with students initially. None.